An infant with kwashiorkor: the forgotten disease - Kamaruzaman, Nor Azam; Jamani, Nurjasmine Aida; Said, Abdul Hadi (Family Medicine Specialist Association, 2020)
Undernutrition remains a major public health concern, especially in developing countries. Despite being rich in resources, Malaysia is still home to children suffering from severe undernutrition. This paper presents the case of a 5-month-old boy with kwashiorkor stemming from improper weaning which was overlooked. This case highlights the importance of recognizing the early signs of kwashiorkor to allow for early referrals for proper management and prevent its possible complications.